Стан та перспективи розвитку SDR технології, як основи сучасних систем зв’язку та радіомоніторингу - Севрюков, О. Ю. (ХНУРЕ, 2025)
Software-Defined Radio (SDR) is an advanced technology in telecommunications, radio monitoring, and wireless systems. It enables flexible signal processing using software instead of traditional hardware modifications. SDR is widely applied in military, mobile networks, satellite communication, and cognitive radio. Key advantages include multi-standard support, adaptive modulation, and real-time reconfiguration. However, SDR faces challenges such as ADC limitations, computational costs, and power consumption. Future developments focus on energy efficiency, AI-based spectrum management, and cloud integration.
Keywords: радіомоніторинг; SDR технології